Re-imaging Palestine in selected poems from Handal’s the lives of rain - Aman, Yasser Khamis Ragab (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper investigates Nathalie Handal’s re-imaging of Palestine as the Promised Land. Such a re-imaging is crystallized through two perspectives: identity politics, which spotlights two distinctively separated groups, viz., the Palestinians and the Israelis, and shared/global identity which depends on transcendence to common humanity. Handal is a French-American poet, born in Haiti to a Palestinian family from Bethlehem. She has lived in different places in Europe, the US and Arab World. She reconstructs an image of Palestine from family memories and from her strong sense of belonging enhanced by frequent journeys to Palestine in the hope that she might have a home in poetry. In many poems such as “Ephratha” , “Bethlehem”, “ Regrets in Galilee”, “Jenin”, “Gaza City”, “Haifa”, “Baladna” and “Amrika” , Handal recalls a geomental image of home. However, a geopolitical image of home is put in juxtaposition in order to highlight Handal’s journey for obtaining global identity. I argue that the two perspectives, which are intricately intertwined in Handal’s poems due to her life and travels, provide a version of complete portrait of Palestine.